Meningeal melanocytes in the mouse: Distribution and dependence on Mitf - Stefan Arni Hafsteinsson Gudjohnsen; Stefan Arni Hafsteinsson Gudjohnsen; Diahann A. M. Atacho; Diahann A. M. Atacho; Franck eGesbert; Graca eRaposo; Ilse eHurbain; Ilse eHurbain; Lionel eLarue; Eirikur eSteingrimsson; Petur Henry Petersen (Frontiers Media S.A., 2015)
Melanocytes are pigment producing cells derived from the neural crest. They are primarily found in the skin and hair follicles, but can also be found in other tissues including the eye, ear and heart. Here we describe the distribution of pigmented cells in C57BL/6J mouse meninges, the membranes that envelope the brain. These cells contain melanosomes of all four stages of development and they depend on MITF, the master regulator of melanocyte development, suggesting that they are bona-fide melanocytes. The location of these pigmented cells is consistent with the location of meningeal melanomas in humans and animal models.